Pengaruh Etika Kerja, Disiplin Kerja Terhadap Kinerja Karyawan PT. Sinar Jaya Inti Mulya - Riyanto, Kuncoro Budi; Sugeng, Sugeng; Wulandari, Suci Ayu (Jurnal Manajemen DIVERSIFIKASI, 2023)
In the modern era and current technological developments, people can carry out activities in amore practical and faster way because of increasingly rapid technological developments. allactivities in kehipuan can be done in a practical and fast way without exception. Coupledwith increasingly sophisticated technology that can help in everyday life. Human resources(HR) is a very important aspect in a company. Therefore, a company must be able to manageHuman Resources as well as possible in order to increase productivity within a company.With good productivity, a company can meet the company's targets that have been set. Goodemployee performance will help employees to meet company targets and also help companiesto earn profits. However, if the performance of the company's employees decreases, it will bedetrimental to the company. This study aims to determine 1) To determine the effect of workethics on employee performance. 2) To determine the effect of work discipline on employeeperformance 3) To determine the effect 4) To determine the effect of work ethics and discipline on employee performance. The survey method was chosen as the primary datasource. The survey method focuses on collecting data from respondents who have certaininformation, thus enabling researchers to solve problems. Data collection was carried outusing a questionnaire or questionnaire instrument. The population in this study wereemployees of PT Sinar Jaya Inti Mulya, totaling 173 people. The data collection techniqueused a questionnaire with a Likert scale. The results show that 1) there is a positive andsignificant influence between work ethics on employee performance 2) there is a positive andsignificant influence between work discipline on employee performance. 4) there is a positiveand significant influence between ethics and work discipline on employee performance